2018
DOI: 10.1111/tid.12992
|View full text |Cite
|
Sign up to set email alerts
|

Impact of antiretroviral regimen on renal transplant outcomes in HIV‐infected recipients

Abstract: Our study suggests that PI-based antiretroviral therapy regimens are associated with improved graft survival and that patients can achieve adequate outcomes on a PI-based regimen when necessary. Due to study limitations, further studies are needed to determine the optimal immunosuppression/antiretroviral therapy regimen post-transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…At these time points, rejection rates were significantly higher with boosted PI ART regimens compared to other HAART regimens, 59% vs 24%. Drug interaction and impact on rejection 24 Report on 50 patients where cumulative rejection rates at 12 and 36 mo were 41% and 54% in the PI group vs 52% and 86% in the non-PI group. At last follow-up, the overall risk of acute rejection in the PI group was 46% lower compared with the non-PI cohort.…”
Section: Drug Interactions and Its Impactmentioning
confidence: 99%
“…At these time points, rejection rates were significantly higher with boosted PI ART regimens compared to other HAART regimens, 59% vs 24%. Drug interaction and impact on rejection 24 Report on 50 patients where cumulative rejection rates at 12 and 36 mo were 41% and 54% in the PI group vs 52% and 86% in the non-PI group. At last follow-up, the overall risk of acute rejection in the PI group was 46% lower compared with the non-PI cohort.…”
Section: Drug Interactions and Its Impactmentioning
confidence: 99%
“…However, use of these agents comes with the risk of adverse effects of immunosuppression (including significant nephrotoxicity and neurotoxicity) and rejection due to potentially subtherapeutic levels while in the dose‐finding stages, as well as difficulty with patient compliance . Encouragingly, Sparkes, et al recently reported data showing reduced renal graft failure rates with PI use at their transplant center . Further research into the close monitoring of tacrolimus in this setting is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Rejection rates were noted to be significantly higher with PI‐boosted regimens at 1, 2, and 3 years (59%‐68%) in a single‐center retrospective study from Rollins and colleagues of 42 HIV+ kidney transplant recipients 34 . In contrast, Sparkes' retrospective cohort study of 50 HIV+ kidney transplant recipients showed lower rejection rates at 1 year in the PI‐based regimen group (41% vs. 52%) 35 . Additionally, PI‐based regimens have been associated with an increased risk of patient death (aHR 1.91, 95% CI 1.02‐3.59) and allograft loss (aHR 1.84, 95% CI 1.22‐2.77) 36 .…”
Section: Hiv and Eskdmentioning
confidence: 95%